2006
DOI: 10.1016/j.pain.2006.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype, dose and sex on pruritogen-induced scratching behavior in the mouse

Abstract: Itch features considerable interindividual variability in humans, and initial studies using animal models have demonstrated a likely role of genetic factors in mediating such variability. In an attempt to systematically study genetic mediation of itch in the mouse such that gene identification by linkage mapping might be achieved, we examined scratching behavior induced by histamine and chloroquine in mice of 11 inbred mouse strains. Multiple chloroquine drug doses were used, revealing the existence of inverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 45 publications
7
64
1
1
Order By: Relevance
“…Histamine elicited dose-dependent scratching ( Fig. 1), confirming previous studies showing robust scratching in ICR mice with variable efficacy in other strains (Inagaki et al, 2001;Green et al, 2006;Shimada and LaMotte, 2008) that is mediated via H1 and H4 histamine receptors (Ohtsuka et al, 2001;Bell et al, 2004). Histamine-evoked scratching exhibited significant tachyphylaxis, consistent with reduced itch sensation upon repeated challenge with histamine in humans (Ståhle-Bä ckdahl et al, 1988).…”
Section: Scratching and Spinal Dorsal Horn Activation In Mice 949supporting
confidence: 86%
See 1 more Smart Citation
“…Histamine elicited dose-dependent scratching ( Fig. 1), confirming previous studies showing robust scratching in ICR mice with variable efficacy in other strains (Inagaki et al, 2001;Green et al, 2006;Shimada and LaMotte, 2008) that is mediated via H1 and H4 histamine receptors (Ohtsuka et al, 2001;Bell et al, 2004). Histamine-evoked scratching exhibited significant tachyphylaxis, consistent with reduced itch sensation upon repeated challenge with histamine in humans (Ståhle-Bä ckdahl et al, 1988).…”
Section: Scratching and Spinal Dorsal Horn Activation In Mice 949supporting
confidence: 86%
“…In contrast, intradermal histamine induces a local flare and itch sensation by exciting a different population of mechanically insensitive C-fiber afferents (Schmelz et al, 1997), as well as mechanosensitive C-fiber nociceptors to varying degrees (Handwerker et al, 1991;Johanek et al, 2008). Histamine also elicits dose-related scratching behavior in ICR mice and variable (or no) scratching in other mouse strains (Kuraishi et al, 1995;Inagaki et al, 2001;Green et al, 2006;Shimada and LaMotte, 2008). Histamine excites lamina I spinothalamic tract neurons in cats over a time course consistent with itch sensation (Andrew and Craig, 2001).…”
mentioning
confidence: 99%
“…Interestingly, histamine-induced itching shows species-specificity. For example, histamine evokes scratching in most mouse strains but little in SpragueDawley rats [27,28] . It is well accepted that a specific sub-class of C-fibers mediates itch and is distinct from that mediating pain [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Because patients experience itch when they first ingest chloroquine and because antihistamines do not effectively prevent this side effect, researchers in Africa concluded that chloroquine-induced itch is not an allergic response, nor is it mediated by histamine receptors (Abila et al 1994). Interestingly, injecting chloroquine into the skin of mice evokes a robust scratching response in the mice, and various inbred strains of mice exhibit different degrees of scratching responses (Green et al 2006). Based on this response, we tested whether our Mrgpr-cluster Δ À/À mice respond differently from wild-type following chloroquine injection.…”
Section: Mrgpra3mentioning
confidence: 99%